VISCOELASTIC AND PROCESSING EFFECTS ON THE FIBER-MATRIX INTERPHASE STRENGTH .2. THE EFFECTS OF CURE TEMPERATURE-TIME AND CURING AGENT CONTENT - TURGUT, A; SANCAKTAR, E (Gordon Breach Sci Publ Ltd, 1992)
[Abstract Not Available]
Keywords: FIBER-MATRIX INTERPHASE; CURE TEMPERATURE CURE TIME CURING AGENT CONTENT SUPERPOSITION; CURE OPTIMIZATION; ADHESIVE VISCOSITY; ADHESIVE MOLECULAR WEIGHT; KINETICS OF WETTING